1997
DOI: 10.1111/j.1745-6584.1997.tb00071.x
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Evaluation of Artificial Recharge Through Percolation Tanks Using Environmental Chloride

Abstract: For meeting the growing demand on ground water in hard rock areas of India, man‐made percolation tanks have become important structures for augmenting ground‐water recharge. Keeping in view their increasing number and cost involved in their construction and their temporal variation in percolation due to silting or desilting operations if undertaken, it is vital to develop proper methodology to evaluate the performance of these structures. A method employing the mass balance of environmental chloride in the tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…These include water harvesting and use of qanats. Rainwater harvesting can be used to recharge groundwater via recharge ponds (Sukhija et al 1997). Qanats are drainage tunnels commonly found in the arid and semi-arid areas of Europe, North Africa and Asia (Castellani & Dragoni 1997;Issar & Zohar 2007).…”
Section: Impacts and Adaptation: Some Topics On Which To Focus Researchmentioning
confidence: 99%
“…These include water harvesting and use of qanats. Rainwater harvesting can be used to recharge groundwater via recharge ponds (Sukhija et al 1997). Qanats are drainage tunnels commonly found in the arid and semi-arid areas of Europe, North Africa and Asia (Castellani & Dragoni 1997;Issar & Zohar 2007).…”
Section: Impacts and Adaptation: Some Topics On Which To Focus Researchmentioning
confidence: 99%
“…Other simple soil models can also be used to estimate water recharge, by calculating how much water is potentially available for groundwater recharge from the differences among the measured rainfall, the estimated actual evapotranspiration and the soil moisture (Ragab et al 1997;Chapman and Malone 2002). As well as the aforementioned physical models, the measured distribution of environmental tracers, 3 H, 36 Cl and chloride, in a soil water profile, have also been used to estimate the rate of movement of water in soil, to locate a groundwater aquifer (Eriksson and Khunakasem 1969;Sukhija et al 1997;Cook and Robinson 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of an artificial recharge structure in hard-rock terrain attempted by Muralidharan and Venugopalan Nair (1998) using tracer studies indicated that only 30-35% is contributed by deep percolation (recharge to groundwater); the rest is accounted for by evaporation loss from storage and soil moisture evaporation loss during recession of storage, as quantified in their investigations. The work carried out by Sukhija et al (1997) using tank-water chloride balance indicated that the percolation efficiency is about 60%. Sukhija et al (1997) also reported that the efficiency reduces in consecutive years due to silt accumulation in the tank bed area.…”
Section: Introductionmentioning
confidence: 99%
“…The work carried out by Sukhija et al (1997) using tank-water chloride balance indicated that the percolation efficiency is about 60%. Sukhija et al (1997) also reported that the efficiency reduces in consecutive years due to silt accumulation in the tank bed area. Among the research needed to gain understanding of the suitability of a site for the construction of a water harvesting structure, infiltration test measurements provide scope for characterizing the efficiency of the site before the construction.…”
Section: Introductionmentioning
confidence: 99%